Capital Adequacy Ratio (Car) dan Faktor-Faktor Yang Mempengaruhinya di Bank Syariah Mandiri (Periode Maret 2012 - Maret 2019) - Ismaulina Ismaulina; Ayu Wulansari; Mira Safira (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2020)
CAR variable is the most important indicator of bank health according to BI. CAR is influenced by NPF, ROA, BOPO, FDR. The problem is how partially the influence of NPF, ROA, BOPO, FDR on CAR in BSM from March 2012-March 2019? Do NPF, ROA, BOPO, FDR simultaneously affect CAR? The research method used is quantitative descriptive with SPPS analysis version 22. The results showed that the NPF value of t-count was 0.449 <t table 1.705, so that it received Ho1 so that it could be concluded that NPF had no effect on CAR at PT. BSM for March 2012-March 2019. While ROA, BOPO and FDR affect the CAR of PT. BSM. This can be seen from the value of each variable at the t-value higher than the t-table value. ROA t-count 2,262> 1,705 t-tables. BOPO value of t-itung 1.916> t-table 1.705. and FDR value t-count -2.969> t-table 1.705, and for the simultaneous test F count> F table (3.286> 2.98) with a significant value of 0.028> α = 5% (0.05). This means that there is a significant influence together between all the independent variables on the dependent variable in PT.BSM.